2020
DOI: 10.1148/ryai.2020190082
|View full text |Cite
|
Sign up to set email alerts
|

Computer-aided Assessment of Catheters and Tubes on Radiographs: How Good Is Artificial Intelligence for Assessment?

Abstract: Catheters are the second most common abnormal finding on radiographs. The position of catheters must be assessed on all radiographs, as serious complications can arise if catheters are malpositioned. However, due to the large number of radiographs performed each day, there can be substantial delays between the time a radiograph is performed and when it is interpreted by a radiologist. Computer-aided approaches hold the potential to assist in prioritizing radiographs with potentially malpositioned catheters for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 43 publications
(40 reference statements)
0
24
0
Order By: Relevance
“…Several studies have been performed for the detection of lines and tubes in chest radiographs [44][45][46][47][48][49]. Generally the algorithms are quite good in classifying the presence versus absence of an endotracheal tube [50], but the systems perform worse when the exact position of the tip of the tube is sought.…”
Section: Lines/tubesmentioning
confidence: 99%
“…Several studies have been performed for the detection of lines and tubes in chest radiographs [44][45][46][47][48][49]. Generally the algorithms are quite good in classifying the presence versus absence of an endotracheal tube [50], but the systems perform worse when the exact position of the tip of the tube is sought.…”
Section: Lines/tubesmentioning
confidence: 99%
“…The authors declare no conflicts of interest. (19), a review article on computer-aided assessment of catheters and tubes where 100 cases were annotated for public use. However, these studies differ from the present work as neither focused on classification of catheter types, nor have the data been previously used to train a CNN.…”
Section: Significance Statementmentioning
confidence: 99%
“…An extensive review of the current state-of-the-art for artificial intelligence applied to catheter assessment was recently published (19), and we refer the reader there for more detail. In brief, there are four main questions related to assessment of catheters on radiographs: i) is there a catheter present?…”
Section: Introductionmentioning
confidence: 99%
“…33 A similar approach has been explored for the detection of endotracheal tubes on adult chest radiographs, achieving an AUROC of 0.99 in classifying the presence of endotracheal tubes. 34 A more in-depth review of the current status of AI for catheter placement assessment can be found in the study by Yi et al 35 In 2019, IBM and MICCAI cohosted the Multimodal Learning for Clinical Decision Support Challenge that was dedicated to catheter detection and classification. 36 Since the data set now is publicly accessible, we expect to see more research regarding assessment of catheters and tubes on radiographs in the near future.…”
Section: Assessment Of Lines and Tubesmentioning
confidence: 99%